1998
DOI: 10.1088/0268-1242/13/11/005
|View full text |Cite
|
Sign up to set email alerts
|

Formation of InAs quantum dots on a silicon (100) surface

Abstract: At moderate arsenic fluxes and substrate temperatures (470 • C) InAs grows on Si (100) surface in the Stranski-Krastanow growth mode with the formation of mesoscopic dislocated clusters on top of a two-dimensional periodically corrugated InAs wetting layer. In contrast, at lower temperatures (250 • C) a dense array of self-organized nanoscale InAs quantum dots of uniform size and shape is formed. These quantum dots, when grown on a Si buffer layer and covered with a Si cap, give a luminescence line at about 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 7 publications
(14 reference statements)
0
24
0
6
Order By: Relevance
“…2 Indeed, such small InAs islands on Si͑100͒ surface have been observed by scanning tunneling microscopy and highresolution transmission electron microscopy ͑HRTEM͒. 3,4 HRTEM investigations of capped InAs/Si structures revealed a high density of coherent InAs clusters with typical dimensions in the 3 nm region at the InAs/Si interface for optimized growth conditions. 5,6 Such samples exhibit a broad photoluminescence ͑PL͒ peak in the 1.3 m region at 10 K. 3 Detailed optical investigations of this PL line indicated a k-indirect type II transition, which has been tentatively attributed to excitons localized in the small coherent InAs clusters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Indeed, such small InAs islands on Si͑100͒ surface have been observed by scanning tunneling microscopy and highresolution transmission electron microscopy ͑HRTEM͒. 3,4 HRTEM investigations of capped InAs/Si structures revealed a high density of coherent InAs clusters with typical dimensions in the 3 nm region at the InAs/Si interface for optimized growth conditions. 5,6 Such samples exhibit a broad photoluminescence ͑PL͒ peak in the 1.3 m region at 10 K. 3 Detailed optical investigations of this PL line indicated a k-indirect type II transition, which has been tentatively attributed to excitons localized in the small coherent InAs clusters.…”
mentioning
confidence: 99%
“…3,4 HRTEM investigations of capped InAs/Si structures revealed a high density of coherent InAs clusters with typical dimensions in the 3 nm region at the InAs/Si interface for optimized growth conditions. 5,6 Such samples exhibit a broad photoluminescence ͑PL͒ peak in the 1.3 m region at 10 K. 3 Detailed optical investigations of this PL line indicated a k-indirect type II transition, which has been tentatively attributed to excitons localized in the small coherent InAs clusters. 7 The extreme small size (Ͻ3 nm) of these clusters might, however, prevent sufficient carrier localization.…”
mentioning
confidence: 99%
“…NWs allow for almost unlimited bottom-up bandgap engineering and can be grown on dissimilar substrates without dislocations [1,2]. For example, it is very difficult to grow defect-free InAs Stranski-Krastanow islands on silicon substrates (lattice mismatch 11.6%) [3], while high quality epitaxial InAs NWs can easily be grown on Si(111) if their diameter is smaller than the critical dimension for plastic relaxation (~ 25 nm) [4]. However, size (length and diameter) uniformity within the NW ensembles remains an issue for various electronic and photonic applications [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, nc-InAs are grown on III-V semiconductor substrates such as GaAs and InP. Some authors report nc-InAs grown on Si [3], but very few studies concern the integration of nc-InAs in SiO 2 . In 2001, Zheng et al [4] have demonstrated the integration of nc-InAs and nc-InAs x P 1À x in SiO 2 by radio-frequency magnetron cosputtering.…”
Section: Introductionmentioning
confidence: 99%